An exploratory study on the intention to use online food delivery among corporate workers / Nur Shahrulliza Muhammad ... [et al.] - Muhammad, Nur Shahrulliza; Mohd Razak, Muhamad Raziq; Ariffin, Shahira; Abdul Manan, Hasman; Hamdan, Fairus (Universiti Teknologi MARA, 2021)
This study is aimed at investigating the determinants of intention-to-use online food delivery (OFD) service among corporate workers in Klang Valley where the market is made up largely of time starved people that are enduring difficulties in balancing working time and rest time or leisure time at their convenience. The research focuses on workers ranging from managers, executives, to junior level employees as well as interns in different corporate companies located in Kuala Lumpur to cover a wider range of audience with different background of working experiences that contribute to the high growth of corporate world. The respondents were 139 of corporate workers. Data processed and interpreted using the SPSS 23.0 in generating the mean and standard deviation of seven respective factors. The result shows that the respondents had moderate intention to use online food delivery service in helping them managing their time. The apps are trusted, provide reliable information and it is statistically proved that the online food delivery improved their quality of life.